Genetic polymorphisms in metabolic pathways of leflunomide in the treatment of rheumatoid arthritis - Soukup, Tomas; Dosedel, Martin; Nekvindova, Jana; Toms, Jan; Vlcek, Jiri; Pavek, Petr (Clinical and experimental rheumatology, 2015)
Leflunomide (LEF) is a disease-modifying anti-rheumatic drug used for treating rheumatoid arthritis (RA). More than 50% of patients are withdrawn from LEF treatment within one year, mainly due to AEs. Importantly, it is not possible to predict which patients will respond to LEF therapy nor if adverse outcome occurs. Pharmacogenetic studies indicate an impact of single nucleotid polymorphisms (SNPs) on the variability in LEF serum levels with potential relevance to effectiveness and tolerability in individual RA patients. In vitro studies have demonstrated that cytochromes P450 (CYPs), mainly CYP1A2, CYP2C19, and CYP3A4, are involved in LEF metabolite activation. It was shown that CYP1A2*1F allele may be associated with LEF toxicity in patients with RA. In case of dihydroorotate dehydrogenase (DHODH) gene SNP (rs3213422, 19C>A), it was shown that C allele may be associated with LEF toxicity and therapeutic effect. Finally, oestrogen receptor genes SNPs in females may be associated with LEF therapy efficacy. In summary, the results of the current studies suggest a possible diagnostic value of genotyping for patients with RA as biomarkers of LEF therapy efficacy or conversely as indicators of serious side effects. In the future, it will be necessary to corroborate these results in studies with larger numbers of patients and longer follow-up. Moreover, it would be appropriate to focus on CYP2C19, ATP5A1 and PKD1L3 genes.
Keywords: receptory pro estrogeny; Isoxazoles; Dihydroorotate Dehydrogenase; Polymorphism, Single Nucleotide; Biotransformation; nádorové proteiny; Humans; ATP Binding Cassette Transporter, Subfamily G, Member 2; Pharmacogenetics; oxidoreduktasy působící na CH-CH vazby; Arthritis, Rheumatoid; antirevmatika; jednonukleotidový polymorfismus; ABC transportéry; rizikové faktory; Phenotype; farmakogenetika; Genotype; lidé; dihydroorotátdehydrogenasa; zvířata; isoxazoly; leflunomid; revmatoidní artritida; Cytochrome P-450 Enzyme System; Isoenzymes; ATP-Binding Cassette Transporters; Receptors, Estrogen; izoenzymy; fenotyp; Oxidoreductases Acting on CH-CH Group Donors; biotransformace; genotyp; Animals; Neoplasm Proteins; ABC transportér z rodiny G, člen 2; Antirheumatic Agents; systém (enzymů) cytochromů P-450; Leflunomide; Risk Factors